ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI KELAPA DI DESA MOUTONG TIMUR KECAMATAN MOUTONG KABUPATEN PARIGI MOUTONG - Arsat, Arsat; Lamusa, Arifuddin; Muis, Abdul (AGROTEKBIS, 2018)
This study aimed to determine income and feasibility of Coconut farmingsystem in East Moutungvillage Moutongsub district of ParigiMoutong district and was carried out from December 2016 - January 2017. Respondents were the coconut farmers in East Moutongvillage wherethe farmer population was 115 people. The methods usedwere the income and feasibility analyses. The study results indicated thatthe income earned bythe coconut farmers in East Moutongwas IDR 6,601,300/0.63ha/year or IDR 10,478,253/ha/year. The coconut farming system was also feasible as shown by the R/C value of 5.98>1 indicating that for each IDR 1,000spent will generate revenue of IDR 5,980.